Politik Pembangunan Organisasi Kemasyarakatan Islam Indonesia – Malaysia - Heri Kusmanto; Warjio Warjio (Universitas Medan Area, 2019)
Politically, Kelantan is unique compared to other states in Malaysia. Manifestations of the doctrine of competition between UMNO and PAS occurred in this last fortress of the Malay states (the last bastions of Malayness). Different political doctrines has caused relations between PAS-led Kelantan State Government and Federal Government, the UMNO-led Alliance, is always hot. But the doctrine of competition began to simmer down, upon the occurrence of the May 13, 1969 event, which allows both parties to come up with a government known as the PAS-Alliance Coalition Government (1973-1974) and later to be replaced by the Barisan Nasional (National Front) Government in 1974. PAS position in the National Front only lasted for three and a half years, when a political turmoil brewed up and has caused the party's expulsion. The expulsion of PAS from the National Front has caused the defeat of PAS to lose Kelantan State Legislative Assembly in the 1978 General Election. This provides the opportunity to the UMNO-led Barisan Nasional to rule Kelantan for 12 years and engage itself in extensive political strategies to defend its position from being constantly attacks by the PAS opposition quarters. However, due to some internal and external problems in the UMNO, PAS has won back the administration of the state of Kelantan by winning State Legislative Assembly in the 1990 general election.